The discourse of colors as a satirical cultural system in the novel “The Book of Judges” by Ahmed Zghab. - Guebna, Said (El Omda in Linguistics and Discourse Analysis, 2023)
This article targets the discourse of colors as a cultural pattern of irony in the diaries of a traditional desert society, in which the social and moral gaps in this type of closed society are evident. The novel " sifr al-khodat " by writer Ahmed Zeghab presents us with dramatic and satirical scenes in the lives of marginalized groups, and it has turned into chronic systemic defects that create a societal paradox, and perhaps cultural criticism makes it easier for us to study and analyze these margins.